A comparative study of simulation results between PHERB, ADVISOR and AUTONOMIE models - J. S. Norbakyah; A. R. Salisa (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
In this research, a new model development and innovation of conventional boat named plug-in hybrid electric recreational boat (PHERB) was introduced to overcome the fuel economy nowadays. This paper focus on the comparison simulation results of PHERB with advanced vehicle simulator (ADVISOR) and an automotive simulation and analysis tool (AUTONOMIE) models in terms of electric machine, energy system storage, propeller and boat model. The model of the PHERB is consequent and applied mathematically in the MATLAB/SIMULINK environment to study its functioning performance. Besides that, fuel economy and emissions of PHERB, ADVISOR and AUTONOMIE model are equated and the pros and cons were discussed in this paper based on simulation result.